Mystery ranch - Warner, Gertrude Chandler, 1890-1979 (Warner, Gertrude Chandler, 1890-1979. Boxcar children mysteries, 2023)
"The Aldens spend the summer on their aunt's ranch! The ranch is a beautiful place, but it's also the source of trouble between Aunt Jane and Grandfather. As the Boxcar Children explore the land, they make an amazing discovery. Will it help mend Aunt Jane and Grandfather's relationship?"--